National Exam Elimination Policy by Student during The COVID-19 Pandemic - Nuha, Zaki Ulien (Ar-Rosikhun: Jurnal Manajemen Pendidikan Islam, 2022)
Abstract. This study aims to find out the impact of the elimination of national examinations according to junior high school students during the covid-19 pandemic in Batu. This type of research is descriptive analysis with qualitative approach. Data analysis in this study uses source triangulation. Data analysis is taken by reducing data, summarizing all data results, and presented in narrative form and then concluded. The number of research subjects was 6 junior high school students in Batu, as well as data collection techniques, namely observation and interviews. Data analysis in this study is in the form of presentation of data in a short description. The results of data analysis showed that in the implementation of national examinations there is a positive impact that students are encouraged to actively study and negative impacts that students experience psychological and mental pressures because they have to master the learning materials to be tested. Students' graduation is seen from the national test scores to apply to the intended school. This happens so that a policy arises that is the elimination of national examinations.Keywords: Policies, National Examinations, Students, Covid-19 Pandemic Period.